Heterotaxia syndrome: the role of screening for intestinal rotation abnormalities. Issue 8 (12th May 2005) - Choi, M; Borenstein, S H; Hornberger, L; Langer, J C
Abstract : Background: Heterotaxia syndrome involves multiple anomalies, including cardiac malformations and intestinal rotation abnormalities. Most authors recommend routine radiological evaluation, with laparotomy and Ladd procedure if a rotation abnormality is found. Aims: To determine if routine radiological screening is necessary, and if there is a group of children that can safely be managed expectantly. Methods: Retrospective chart review of all children with heterotaxia syndrome from 1968 to 2002. Results: Complete data were available for 177 patients. Twenty five (14%) had neonatal gastrointestinal symptoms (feeding intolerance, vomiting). Eleven of these had gastrointestinal contrast studies, of which seven were abnormal and led to surgery. Of the 152 asymptomatic neonates, nine had radiological screening and six of these were abnormal. Only one was thought to have a narrow based mesentery, but did not undergo surgery due to cardiac disease. There were no intestinal complications on follow up in this group. The other 143 asymptomatic children did not undergo radiological screening and were closely followed. Four subsequently developed gastrointestinal symptoms and had contrast studies; only one of these had malrotation and underwent a Ladd procedure. Of the remaining 139 patients who remained asymptomatic, 60 (43%) died of cardiac disease and none developed intestinal symptoms or complications related to malrotation on follow up. Conclusion: Asymptomatic children with heterotaxia syndrome have a low risk of adverse outcome related to intestinal rotation abnormalities. Routine screening may not be necessary as long as close follow up is done, and prompt investigation is performed for those that develop gastrointestinal symptomatology.